Management of Maternal Cardiac Arrest in the Third Trimester of Pregnancy: A Simulation-Based Pilot Study - Jacquelyn Adams; Jose R. Cepeda Brito; Lauren Baker; Patrick G. Hughes; M. David Gothard; Michele L. McCarroll; Jocelyn Davis; Angela Silber; Rami A. Ahmed (Critical Care Research and Practice)
Objective. To evaluate confidence, knowledge, and competence after a simulation-based curriculum on maternal cardiac arrest in an Obstetrics & Gynecologic (OBGYN) residency program. Methods. Four simulations with structured debriefing focusing on high yield causes and management of maternal cardiac arrest were executed. Pre- and post-individual knowledge tests (KT) and confidence surveys (CS) were collected along with group scores of critical performance steps evaluated by content experts for the first and final simulations. Results. Significant differences were noted in individual KT scores (pre: 58.9±8.9 versus post: 72.8±6.1, p=0.01) and CS total scores (pre: 22.2±6.4 versus post: 29.9±3.4, p=0.007). Significant differences were noted in airway management, p=0.008; appropriate cycles of drug/shock-CPR, p=0.008; left uterine displacement, p=0.008; and identifying causes of cardiac arrest, p=0.008. Nonsignificant differences were noted for administration of appropriate drugs/doses, p=0.074; chest compressions, p=0.074; bag-mask ventilation before intubation, p=0.074; and return of spontaneous circulation identification, p=0.074. Groups remained noncompetent in team leader tasks and considering therapeutic hypothermia. Conclusion. This study demonstrated improved OBGYN resident knowledge, confidence, and competence in the management of third trimester maternal cardiac arrest. Several skills, however, will likely require more longitudinal curricular exposure and training to develop and maintain proficiency.